A cross-sectional survey to assess the effect of socioeconomic status on the oral hygiene habits - Sukhvinder Singh Oberoi; Gaurav Sharma; Avneet Oberoi (Wolters Kluwer Medknow Publications, 2016)
Background: It is widely accepted that there are socioeconomic inequalities in oral health. A socioeconomic gradient is found in a range of clinical and self-reported oral health outcomes. Aim: The present study was conducted to assess the differences in oral hygiene practices among patients from different socioeconomic status (SES) visiting the Outpatient Department of the Sudha Rustagi College of Dental Sciences. Materials and Methods: A cross-sectional survey was conducted from June to October 2014 to assess the effect of SES on the oral hygiene habits. The questionnaire included the questions related to the demographic profile and assessment of the oral hygiene habits of the study population. Results: Toothbrush and toothpaste were being used significantly (P < 0.05) more by lower middle class (84.4%) and upper middle class (100.0%). A significantly higher frequency of cleaning teeth (twice a day) was reported among the lower middle class (17.2%) and upper middle class (21.5%). The majority (34.3%) of the study population changed their toothbrush once in 3 months. The cleaning of tongue was reported by patients belonging to the upper middle (62.0%), lower middle (52.1%), and upper lower class (30.0%). The use of tongue cleaner was reported to be significantly (P < 0.05) more among upper middle (10.1%) class patients. A significantly higher number of patients from the lower class (81.3%) never visited a dentist. Conclusion: The oral hygiene practices of the patients from upper and lower middle class was found to be satisfactory whereas it was poor among patients belonging to lower and upper lower class.